Tiley's revenue law. - Loutzenhiser, Glen (Hart, 2022)
This edition has been extensively revised to incorporate changes wrought by successive Finance Acts as well as the Inland Revenue's tax law rewrite. It also covers income tax, capital gains tax, corporation tax and inheritance tax.